Konsep Seling dan Marketing - Irna Ardilla; Nuri Aslami (Transformasi Manageria: Journal of Islamic Education Management, 2022)
Abstract In general, the design of organizational principles obtains certain benefits or improvements to the most extreme that can be expected, and supports to further advance the situation of the organization in seeking its long-term goals. The reason can be achieved if the sale of the organization is held on what has been arranged and this has been arranged beforehand. Therefore, this does not mean that every product or service of the organization that is purchased by the client, will always bring financial benefits to the organization. Around here, there are several variables that the organization should pay attention to. Sfudy Day and Nedimgodi clarified that organizations that can handle the market; referred to as a morkef-driven company; Is an organization that can adjust both directions well, with superior promotional performance results, compared to other companies. Coordination between capacities within the organization in an effort to share client and competitor data, to face more complicated competition. Keywords : selling and marketing